BIMBINGAN BELAJAR KELOMPOK DALAM BERKARYA SENI TARI SEDERHANA DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA KELAS X IPA 3 SMA NEGERI 8 DENPASAR TAHUN AJARAN 2016/2017 - Ni Nyoman Puspadi (Widyadari : Jurnal Pendidikan, 2021)
This classroom action research aims to determine the increase in student achievement in the subject of dance and culture in class X IPA 3 SMA Negeri 8 Denpasar, after being given group guidance. The subjects of this study were 4 out of 40 students. These students have low learning achievement by showing symptoms of not being interested in receiving lessons, students find it difficult to learn and master dance lessons, study irregularly, often do not do assignments, do not want to ask passively in following lessons. This research was conducted in 2 cycles where each cycle was allocated 1 month and 8 meetings. The method used to monitor the implementation of actions and the results achieved from these actions is the method of observation which contains an observation guide. The results of the analysis showed that in the first cycle of 4 students who were subjected to action there were 2 people who had not shown an increase in learning motivation. For this reason, 2 people whose cases were given action in cycle II, and 2 students who had shown increased motivation in cycle I also experienced an increase in this second cycle. By consistently providing group study guidance, it turned out that 4 students who were subjected to action showed an increase in learning achievement. The percentage increase in student learning achievement subject to action is in the first cycle the average increase is 50%, the second cycle is 68.4% and the cycle. As an impact of an increase in student learning outcomes followed by an increase in learning achievement in the subject of Dance and Culture. From the results of the analysis it can be concluded that by providing group guidance regularly and continuously will be able to increase student learning motivation, which in turn will be able to increase achievement. learn it.